Effect of integrated nutrient management on the yield, yield attributes and protein content of lentil (Bangladesh Journal of Agricultural Research, 2019)
A field experiment was conducted at the Pulse Research Sub-station of Bangladesh Agricultural Research Institute (BARI), Gazipur during rabi season of 2015-16 and 2016-17 to evaluate the effectiveness of organic and inorganic sources of nutrients in terms of growth and yield maximization of lentil. The experiment was laid out in a randomized complete block design (RCBD) having six treatments with three replications. The treatments were T1= Recommended dose (N20P15K30S10Zn3B1.5 kg ha-1), T2= IPNS (Inorganic) +2.5 t ha-1cowdung, T3= IPNS (Inorganic) +5 t ha-1cowdung, T4= IPNS (Inorganic) +1.5 t ha-1 poultry manure, T5= IPNS (Inorganic)+3 t ha-1 poultry manure and T6= Control. The results reveal that the integrated nutrient management had significant effects on the plant height, number of branches per plant, number of pods per plant, number of seeds per pod, 1000-seed weight, and seed yield of lentil. The maximum seed yield (1216 kg ha-1) as well as protein content (26.1%) were recorded with T4 treatment. The results advocate that satisfying the recommended dose through application of poultry manure @ 1.5 t ha-1 with IPNS inorganic fertlizer could be suggested for achieving yield miximization of lentil in chhiata soil series of Gazipur.Bangladesh J. Agril. Res. 44(3): 525-536, September 2019